2005
DOI: 10.1007/s00442-005-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

Seed weight increases with altitude in the Swiss Alps between related species but not among populations of individual species

Abstract: Seed weight is a crucial plant life history trait, determining establishment success and dispersal ability. Especially in stressful environments, larger seeds may be selected at the expense of seed number, because larger seeds have a better chance of giving rise to an established offspring. We tested the hypotheses that between related species-pairs and among populations of single species a similar trend for increasing seed weight with increasing altitude should be present. Firstly, we measured seed weights fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 44 publications
4
101
1
2
Order By: Relevance
“…There are two reasons explaining the absence of legumes from the initial sites. First, many legumes like Lotus alpinus form heavier seeds than L. alpina or C. uniflorum (Pluess et al, 2005;Tackenberg and Stöcklin, 2008), and thus dispersal via wind is more difficult. Second, the establishment and maintenance of a rhizobia-legume symbiosis is a very energy consuming process (Merbach et al, 1999), and therefore energy consumption might be too high under these harsh conditions.…”
Section: Role Of Plantsmentioning
confidence: 99%
“…There are two reasons explaining the absence of legumes from the initial sites. First, many legumes like Lotus alpinus form heavier seeds than L. alpina or C. uniflorum (Pluess et al, 2005;Tackenberg and Stöcklin, 2008), and thus dispersal via wind is more difficult. Second, the establishment and maintenance of a rhizobia-legume symbiosis is a very energy consuming process (Merbach et al, 1999), and therefore energy consumption might be too high under these harsh conditions.…”
Section: Role Of Plantsmentioning
confidence: 99%
“…Makin tinggi tempat tumbuh menghasilkan benih yang makin berat dan makin lebar (Gambar 1), namun untuk karakter morfologi lainnya (panjang, tebal, dan tebal kulit benih) tidak menunjukkan adanya korelasi yang kuat dengan faktor lingkungan (curah hujan dan ketinggian tempat). Beberapa penelitian melaporkan berat benih meningkat dengan meningkatnya ketinggian tempat, yaitu pada (Loha ., 2006), (Ayana dan Bekele, 2000), dan (Boulli ., 2001), namun pada beberapa jenis juga tidak menunjukkan korelasi yang signifikan seperti pada (Holm, 1994), (Totland dan Birks, 1996) (Pluess ., 2005). Variasi morfologi dan berat benih selain dipengaruhi oleh faktor lingkungan juga dikontrol oleh faktor genetik (Mkonda ., 2003), dimana pada jenis dengan keragaman genetik yang rendah kemungkinan sedikit sekali perbedaan karakter morfologi antar kelompok benih tersebut.…”
Section: A 2 4 J a M ( A 5 )unclassified
“…However, successive studies have either rejected (Mariko et al, 1993;Pluess et al, 2005) or accepted (Bu et al, 2007b;Guo et al, 2010;Dainese and Sitzia, 2013) this proposition, thereby undermining the generality of this pattern. One plausible reason for lack of unanimity in results is because in these studies the climatic conditions in which the seeds have developed were poorly measured or ignored.…”
Section: Vaccinium Myrtillus Rhinanthus Minor Rumex Acetosa Cicerbmentioning
confidence: 99%
“…For Baker (1972) the average seed weight of species occurring at a particular altitude compared with the mean seed weight at a different (higher) altitude shows a decreasing trend, although discussions on one (Penstemon) genera and possibly same results on other genera were presented. Pluess et al (2005) measured the seed size in 29 Swiss alpine congeneric species and found seed size increased with altitude for 55% of the species tested, but decreased or remained equal for 3% and 41% of species respectively. Nevertheless, populations of Scabiosa lucida, Saxifraga oppostifolia, Epilobium fleischeri and Carex flaccafound occurring at different altitudes showed a decrease in seed size with altitude.…”
Section: Vaccinium Myrtillus Rhinanthus Minor Rumex Acetosa Cicerbmentioning
confidence: 99%